PEMANFAATAN HYPERTEXT DALAM PEMBELAJARAN - Rufman Imam Akbar (SISFOTENIKA, 2012)
Abstract : Technological developments, especially the application of information technology is developing very rapidly once. Information technology in use in almost all fields, including education. With regard to the limited knowledge in the application, often of technologies is used only as a complement to the learning process - for example, only for the presentation only. This paper attempts to look beyond the possibility of making use of this technology in the learning design. SBC in the application of current curricula, this technology could be more profound through its use in instructional design. Researchers try to discuss HTML implemented in Hypertext Design System. With the background of the development of hypertext theory and learning theory, the authors argue that hypertext can be applied in the learning process through the utilization of the hypertext system design. Keywords : Hypertext System Design, KTSP, learning